A nanostructure platform for live-cell manipulation of membrane curvature - Li, Xiao (2021)
Membrane curvatures are involved in essential cellular processes, such as endocytosis and exocytosis, in which they are believed to act as microdomains for protein interactions and intracellular signaling. These membrane curvatures appear and disappear dynamically, and their locations are difficult or impossible to predict. In addition, the size of these curvatures is usually below the diffraction limit of visible light, making it impossible to resolve their values using live-cell imaging. Therefore, precise manipulation of membrane curvature is important to understanding how membrane curvature is involved in intracellular processes. Recent studies show that membrane curvatures can be induced by surface topography when cells are in direct contact with engineered substrates. Here, we present detailed procedures for using nanoscale structures to manipulate membrane curvatures and probe curvature-induced phenomena in live cells. We first describe detailed procedures for the design of nanoscale structures and their fabrication using electron-beam (E-beam) lithography. The fabrication process takes 2 d, but the resultant chips can be cleaned and reused repeatedly over the course of 2 years. Then we describe how to use these nanostructures to manipulate local membrane curvatures and probe intracellular protein responses, discussing surface coating, cell plating, and fluorescence imaging in detail. Finally, we describe a procedure to characterize the nanostructure-cell membrane interface using focused ion beam and scanning electron microscopy (FIB-SEM). Nanotopography-based methods can induce stable membrane curvatures with well-defined curvature values and locations in live cells, which enables the generation of a library of curvatures for probing curvature-related intracellular processes.